Implementasi dan Pengungkapan Good Corporate Governance pada Bank Umum Syariah Milik BUMN - Masiyah Kholmi (Universitas Muhammadiyah Malang, 2024)
Purpose: This research aims to analyze the implementation and disclosure level of good corporate governance of the state-owned Commercial Bank Sharia in Indonesia 2017-2020 Methodology/Approach: This research uses a content analysis method. The data was collected using documentation techniques in the form of annual the state-owned Commercial Bank Sharia reports on the websits of each bank. Findings: The research results show that the state-owned commercial bank sharia has implemented and expressed good corporate governance. BNI Sharia and BRI Sharia are included in the